Concussion management in soccer - Jason P. Mihalik; Robert C. Lynall; Elizabeth F. Teel; Kevin A. Carneiro (Elsevier, 2014)
Brain injuries in sports drew more and more public attentions in recent years. Brain injuries vary by name, type, and severity in the athletic setting. It should be noted, however, that these injuries are not isolated to only the athletic arena, as non-athletic mechanisms (e.g., motor vehicle accidents) are more common causes of traumatic brain injuries (TBI) among teenagers. Notwithstanding, as many as 1.6 to 3.8 million TBI result from sports and recreation each year in the United States alone. These injuries are extremely costly to the global health care system, and make TBI among the most expensive conditions to treat in children. This article serves to define common brain injuries in sport; describe their prevalence, what happens to the brain following injury, how to recognize and manage these injuries, and what you can expect as the athlete recovers. Some return-to-activity considerations for the brain-injured athlete will also be discussed.